Oxytocin Protects Rat Skeletal Muscle Against Ischemia/Reperfusion Injury - ERCAN, FERİHA (ELSEVIER SCIENCE INC, 2013)
Background: Oxytocin (OXY) is a well-known nonapeptide that functions in reproduction. It is also known as an antioxidant in several organs. However, little is about its role in the protection of tissue against ischemiareperfusion injury in skeletal muscle. The aim of this study was to evaluate the protective and therapeutic antioxidant effect of oxytocin in skeletal muscle during ischemiareperfusion (IR) injury. Methods: Rats were divided into 4 groups. Hindlimb ischemia was achieved by clamping the common femoral artery in 3 of the groups, but not a control group. OXY was injected before ischemia in the preoperative (preop) IR + OXY group and after the onset of ischemia in the postoperative (postop) IR + OXY group. Saline solution was injected in the IR group. Limbs were rendered ischemic for 90 min. At the end of 90-min reperfusion period, skeletal muscle tissue samples were taken from the ischemic muscle for evaluation at light and transmission electron microscopic levels. Biochemical analysis was done for malonedialdehyde and glutathione levels. Caspase immunohistochemistry was applied for apoptosis. Results: The light- and electron-microscopic scores of the OXY-treated groups were significantly lower than in the IR group. The degree of tissue damage was ameliorated in the OXY-treated groups. The number of apoptotic cells was decreased in the OXY-treated groups compared with the IR group. In OXY-treated groups, the malonedialdehyde level was lower than in the IR group. Glutathione levels were found to be increased in the OXY-treated groups compared with the IR group. Conclusions: Oxytocin has a protective effect against IR injury in skeletal muscle and may reduce the incidence of compartment syndrome.
Keywords: ISCHEMIA-REPERFUSION INJURY; LIVER ISCHEMIA; NEUTROPHILS; MECHANISMS; MELATONIN; STRESS; ACID; SITE